Model of information object for digital library and its verification - Novitsky, A.V.; Reznichenko, V.A. (Інститут програмних систем НАН України, 2020)
An approach for formal verification of UML 2.0 using mapping OWL-DL in UML 2.0 is proposed. As a result, an original approach for mapping OWL-DL to UML 2.0 through description logic has been proposed. The completeness of the mapping of UML-OWL through stereotypes and labeled UML 2.0 values at the level of M0, M1 of the MOF metamodel is provided. A model of the information object (IO) for the semantic electronic library, which is described by using the UML language, is proposed. The proposed IO model was also verified by mapping it into OWL and then validating the constructed ontology by using risoners.Problems in programming 2020; 2-3: 31-38